An Adaptive Secure Timestamp-Based Replay Attack Detection System For Wsns - Babu, G Nagendra; Krishna, Konda Hari; Rao, K Venkateswara (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Wireless Sensor Networks (WSNs) are essential in many fields because they enable real-time data gathering and transmission possible for a wide range of applications. Replay attacks pose significant risks to the integrity and dependability of WSNs, which have become increasingly important due to growing dependence on them. In order to successfully reduce replay attacks in WSNs, this investigation suggests the Adaptive Secure Timestamp-Based Replay Attack Detection System (AST-RADS). Combining cryptographic methods, AST-RADS offers a multi-layered defense system. To guarantee data confidentiality and integrity during transmission, the model uses secure timestamp-based authentication, encryption, and a hierarchical key management system. Additionally, the suggested model is created with minimal overhead, making it appropriate for WSN situations with limited resources. Extensive simulations and experiments validate the efficacy and efficiency of AST-RADS compared to existing solutions, demonstrating its superiority in detecting and preventing replay attacks.